Penerapan Metode Tilawati dalam Pembelajaran Membaca Al-Qur’an pada Ibu Rumah Tangga - Sabila Ulinnuha; Fathul Janah; Abdul Basith (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2022)
The background of this research is the author's interest in the tilawati method used in attracting the attention of the community in addition to filling spare time to take part in learning the Koran. This method offers advantages in the learning process and with the results obtained later, ranging from understanding makharijul uruf, ifatul uruf, gharib musykilat, to understanding tajwid law. The formulation of the research problem is how to apply the tilawati method in learning to read the Koran to housewives at the Jami' Nurul Muhajirin mosque, Mulawarman Tenggarong Seberang village. The purpose of the study was to determine the application of the tilawati method in learning to read the Koran to housewives at the Jami' Nurul Muhajirin mosque, Mulawarman village, Tenggarong Seberang. This type of research is a qualitative descriptive field research, taking the research location at the Jami' Nurul Muhajirin mosque, Mulawarman village, Tenggarong Seberang. Data was collected by using observation, interview, and documentation techniques. The informants are the director and administrator of the Tilawati Education Center (TEC) Mulawarman, educators and students. The steps in analyzing the data include data collection, data condensation, data presentation and data verification. Test the validity of the data using triangulation techniques. The results of the research showed that the application of the tilawati method in learning to read the Koran for housewives at the Jami' Nurul Muhajirin Mosque, Mulawarman Village, Tenggarong Seberang, were: 1. The application of the tilawati method through a classical approach, namely educators reading students imitated and read together. 2. The application of the tilawati method through an individual approach, where students take turns reading each line. In its application, there are things that have not been fulfilled, such as the use of achievement books and memorization material books, as well as the target time of the Koran so that it has not yet reached completion. However, the target time for the volume remains in accordance with the provisions set by the central tilawati institute. This tilawati method is very suitable to be taught to housewives with a gradual (slow) system. So that the application of the tilawati method by the Mulawarman TEC institution can improve the ability to read the Koran in Mulawarman Village housewives